Nekaj razmišljanj o filoloških konceptih Matije Murka - Pospíšil, Ivo (Primerjalna književnost, 2012)
This study analyzes Matija Murko's philological concepts as embodied in two of his early studies of Jan Kollár and the Russian novel, demonstrating Murko's consistent and complex philological approach and his skeptical, rational, genetic method of research.
Keywords: Murko, Matija, 1861-1952; slovenski literarni zgodovinarji; slovanska filologija; Slavic studies; slavistika; panslavizem